Perubahan Fonem-Fonem Bahasa pada Penderita Labioschisis (Bibir Sumbing) pada Podcast Youtube Raditya Dika: Davi Siumbing Ngomongin Nopek - Madalena, Fina Dyah; Suroso, Eko (Ruang Kata, 2025)
This study aims to describe the phonemic changes experienced by people with cleft lip by analyzing the phonemic pronunciation produced by them. The data in this study consists of utterances produced by people with cleft lip. The data source in this study is a person with cleft lip. This study was conducted using a qualitative descriptive method. Data collection techniques were carried out using observation and note-taking techniques. Data analysis was conducted by listening to a video recording from Radita Dika's YouTube podcast titled Davi Siumbing Ngomongin Nopek, then transcribing the patient's speech into written form. After the speech transcription data was obtained, the next step was to analyze the data based on phoneme changes and articulation errors, thereby answering the research questions posed in this study. The results of the study showed that there were types of phoneme changes that occurred, such as deletion, distortion, addition, and substitution. Patients with cleft lip had difficulty producing sounds that involved the meeting of the upper and lower lips, such as /p/, /b/, and /m/. Another difficulty is experienced in the pronunciation of phonemes that require air pressure from the roof of the mouth, such as /d/, /g/, /b/, /j/, /k/, /n/, /p/, and /t/. In addition, pronunciation variations experience changes or omissions of phonemes in some of the words produced. These changes can occur at the beginning, middle, or end of a word, leading to misunderstandings of meaning for listeners